Sufi Hermeneutics of Serat Dewa Ruci in the Age of Information Overload - Rahmah, Farida; Malihatunnajiah, Eneng (Tashwirul Afkar, 2026)
This study aims to reinterpret Serat Dewa Ruci as a symbolic-spiritual text that is relevant to understanding contemporary problems of digital literacy, particularly in situations of information overload, misinformation, and post-truth. The study is significant because scholarship on Serat Dewa Ruci, Islamic Sufism, and digital literacy has largely developed in separate directions, with few integrative readings that bring these three domains into a single analytical framework. This research employs a qualitative library-based approach, with Serat Dewa Ruci as the primary unit of analysis. Data were collected through documentary study of primary and secondary sources and were analysed using hermeneutic and semiotic approaches in order to interpret the text’s symbolic structure, spiritual meaning, and contextual relevance. The findings show that Bima’s journey is constructed as a symbolic progression from outward searching to inward disclosure, while his encounter with Dewa Ruci forms an epistemic discipline that emphasises humility, inward deepening, the ability to interpret signs, and ethical readiness in receiving truth. In the contemporary context, this symbolic structure has strong relevance for strengthening digital literacy, as it offers a model of knowledge grounded in caution, verification, clarity of interpretation, and ethical responsibility. The implication of this study is that digital literacy should be developed not merely as a technical competence, but also as a hermeneutic, ethical, and spiritual practice. The originality of this research lies in its effort to bring together Serat Dewa Ruci as a text of Javanese culture, Islamic Sufism as a spiritual-epistemic framework, and digital literacy as a contemporary problem of knowledge within a single integrative reading.